IMPLIKASI HUKUM KEDUDUKAN PERSEROAN TERBATAS PERORANGAN SEBAGAI SUATU ENTITAS BISNIS YANG BERSTATUS BADAN HUKUM PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA - Nurul Laylan Hsb (Yurisprudentia: Jurnal Hukum Ekonomi, 2025)
The enactment of Law Number 6 of 2023, which ratifies Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation, marks a significant development in the legal framework for business entities in Indonesia. One of the notable reforms is the formal recognition of the Individual Limited Liability Company (ILLC) as a legal entity. This model allows a single individual to establish a company with limited liability status, departing from the traditional requirement of multiple founders. This study examines the legal implications of recognizing the ILLC as a legal entity, particularly in terms of legal responsibility, asset separation, and the protection of business actors. Using a normative legal research method with a statutory and conceptual approach, this study finds that while the ILLC provides flexibility and legal certainty for micro and small-scale entrepreneurs, it also poses challenges related to regulatory oversight and potential misuse due to the absence of internal corporate governance mechanisms. To ensure the effectiveness and accountability of ILLCs in practice, further regulatory refinement and supervisory measures are necessary.